A Brief Review on Activated Carbon Derived From Agriculture By-Product - Yahya, MA; Mansor, MH; Zolkarnaini, WAAW; Rusli, NS; Aminuddin, A; Mohamad, K; Sabhan, FAM; Atik, AAA; Ozair, LN (Amer Inst Physics, 2024)
A brief review focusing on preparation of the activated carbon derived from agriculture by-products is presented. The physical and chemical activation of activated carbon were also reviewed. The effects of various parameters including types of activating agents, temperature, impregnation ratio, were also discussed. The applications of activated carbon from agricultural by products were briefly reviewed. It is provenly evident in this review, the relatively inexpensive and renewable resources of the agricultural waste were found to be effectively being converted into wealth materials.